Chemotherapy in Patients with Progressive, Undifferentiated Neuroendocrine Tumors: A Single-Center Experience - Deutschbein, T.; Unger, N.; Yuece, A.; Eberhardt, W.; Gauler, T.; Lahner, H.; Mann, K.; Petersenn, S. (Hormone and Metabolic Research, 2011)
Treatment of patients with undifferentiated and histologically confirmed neuroendocrine tumors (NET) usually includes chemotherapeutic intervention. This retrospective study evaluated the outcome of 2 such chemotherapies. 18 patients (11 males; age 56.2±2.5) with proven progressive disease were enrolled (mean Ki-67 34±5%). Patients were treated from 2005 to 2007 with regimen A (carboplatin, etoposide, paclitaxel), and from 2007 to 2009 with regimen B (cisplatin, etoposide). This change was due to low tolerability of regimen A. The standard imaging procedure was computed tomography. 8 patients underwent treatment with regimen A (mean 3.3±0.7 courses). Due to severe side effects, 3 patients had their therapy prematurely discontinued. The treatment responses of 6 patients who received more than 1 course were: 0% complete response (CR), 17% partial response (PR), 50% stable disease (SD), and 33% progressive disease (PD). The median progression free survival (PFS) was 6.7 months (range 3.2–10.0). In contrast, 12 patients received regimen B (mean 3.8±0.4 courses), and none of them dropped out because of side effects. The overall responses were: 0% CR, 17% PR, 42% SD, and 42% PD. The median PFS was 6.3 months (range 2.8–26.4). The response rates of both regimes were not statistically different. Patients who were treated with regimen B demonstrated comparable PFS and less severe side effects than patients who received regimen A. However, patients need to be aware of the relatively short PFS time. In order to improve therapeutic outcome of patients with progressive undifferentiated NET, new therapeutic approaches and larger multi-center studies are needed.
Keywords: carboplatin; cisplatin; etoposide; paclitaxel; NET; side effects; toxicity